Part-time work in Europe European Company Survey 2009 - Sandore, Eszter; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2011)
Part-time employment has been increasing in Europe for the past two decades. This is especially true for countries where different working time arrangements have been discussed among policymakers and social partners as a way to increase flexibility. Part-time work, in the widest sense, may have both positive and negative effects for workers and employers. While some workers view it as a solution for balancing work and family life in certain life phases, other part-timers complain of various disadvantages at work compared to full-time workers. It is often argued that there are no available positions for high qualified people wishing to work part-time. For employers, part-time work may have an important use in the work cycle, but it may also mean increased labour costs. This report tries to bring together the results of two European-wide surveys to provide a snapshot of part-time work - presenting both the company and the employee point of view.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Part-time employment -- Europe; Electronic books